Impact of aortic root surgery during transcatheter aortic valve explantCentral MessagePerspective - Alexander P. Nissen, MD; Stephanie K. Tom, MD; R. Michael Reul, MD; Elizabeth L. Norton, MD; Dale S. Deas, MD; Bradley G. Leshnower, MD; Gaetano Paone, MD; W. Brent Keeling, MD; Woodrow J. Farrington, MD; Jonathan R. Zurcher, MD; Robert A. Guyton, MD; Kendra J. Grubb, MD, MHA (JTCVS Structural and Endovascular)
Background: Transcatheter aortic valve replacement (TAVR) explantation is currently the fastest-growing cardiac surgery procedure. Issues surrounding TAVR explantation and subsequent surgical aortic valve replacement (SAVR), specifically aortic root surgery, merit further investigation. Methods: A retrospective review of an institutional database identified cases of SAVR after TAVR, with or without concomitant aortic root operations, performed between January 1, 2014, and July 1, 2023, identifying 26 patients. Conventional statistical methods were used to compare groups. Results: The mean Society of Thoracic Surgeons predicted risk of mortality for aortic valve replacement was 11.1 ± 6.0% in our cohort. Eight of 26 patients (30.8%) had undergone prior cardiac surgery. Concomitant aortic root enlargement or replacement was required in 12 of the 26 patients (46.2%). The time from TAVR to removal was longer for those requiring root operations compared to those who did not (mean, 783 ± 908 days vs 492 ± 486 days; P = .046). There was a trend toward more frequent infective endocarditis in patients requiring root operations (46.2% [n = 5/12] vs 21.4% [n = 3/14]; P = .155). The 30-day mortality was 19.2% (n = 5/26), with an observed-to-expected ratio of 1.72. Mortality was not significantly different between the 2 groups. Conclusions: TAVR explant remains a high-risk procedure, although adding aortic root enlargement/replacement does not appear to amplify the short-term mortality risk when performed at an experienced institution. These results are important when considering lifetime management of aortic stenosis, particularly in low-risk patients likely to require multiple interventions.